2014
DOI: 10.1016/j.antiviral.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Pyridinyl imidazole inhibitors of p38 MAP kinase impair viral entry and reduce cytokine induction by Zaire ebolavirus in human dendritic cells

Abstract: Antigen presenting cells (APCs), including macrophages and dendritic cells, are early and sustained targets of Ebola virus (EBOV) infection in vivo. Because EBOV activates mitogen-activated protein kinase (MAPK) signaling upon infection of APCs, we evaluated the effect of pyridinyl imidazole inhibitors of p38 MAPK on EBOV infection of human APCs and EBOV mediated cytokine production from human DCs. The p38 MAPK inhibitors reduced viral replication in PMA-differentiated macrophage-like human THP-1 cells with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 58 publications
(77 reference statements)
2
45
0
Order By: Relevance
“…We have previously summarized the numerous small molecules described in the literature as possessing antiviral activity that could be further evaluated for their potential EBOV activity alongside the few new antivirals. We have found that there is considerable prior knowledge regarding these small molecules possessing activity against EBOV in vitro or in animal models 58 , and this includes a number of accessible FDA-approved drugs 2, 3, 9 . Another recent study has shown three approved ion channel blockers (amiodarone, dronedarone, and verapamil) inhibited EBOV cellular entry 9 .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously summarized the numerous small molecules described in the literature as possessing antiviral activity that could be further evaluated for their potential EBOV activity alongside the few new antivirals. We have found that there is considerable prior knowledge regarding these small molecules possessing activity against EBOV in vitro or in animal models 58 , and this includes a number of accessible FDA-approved drugs 2, 3, 9 . Another recent study has shown three approved ion channel blockers (amiodarone, dronedarone, and verapamil) inhibited EBOV cellular entry 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Ebola virus disease is associated with an excessive inflammatory cytokine response; therefore, therapies that can control this host response may prove clinically beneficial. Recently, p38 MAPK inhibitors, particularly the standard compound SB202190, have been shown to inhibit Ebola virus-mediated cytokine production from human monocyte-derived dendritic cells in vitro (86). A series of pyridinyl imidazole inhibitors of p38 MAPK (e.g., SB202190 and p38inK III) inhibited viral entry into dendritic cells (86).…”
Section: Repurposing Existing Drugs For Treatment Of Ebola Patientsmentioning
confidence: 99%
“…Recently, p38 MAPK inhibitors, particularly the standard compound SB202190, have been shown to inhibit Ebola virus-mediated cytokine production from human monocyte-derived dendritic cells in vitro (86). A series of pyridinyl imidazole inhibitors of p38 MAPK (e.g., SB202190 and p38inK III) inhibited viral entry into dendritic cells (86). In line with the proinflammatory function of MAPK, dosing of the MAPK inhibitors resulted in much-reduced cytokine and chemokine release levels upon Ebola virus infection, an important feature to minimize Ebola virus virulence.…”
Section: Repurposing Existing Drugs For Treatment Of Ebola Patientsmentioning
confidence: 99%
“…Several promising therapeutic candidates are currently being investigated, but none are FDA approved. Strategies such as treatment with antisense oligonucleotides, antibody-based therapies, and treatment with small molecules directed against specific viral as well as cellular factors have been tested, but the outcomes have been mixed (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Additionally, many of these therapies target only closely related strains of Ebola virus, making the development of treatments for other species of Ebola virus and Marburg virus a priority.…”
mentioning
confidence: 99%